Polyimide adhesive for power storage device, electrode mixture paste, negative electrode active material layer, negative electrode sheet for power storage device, and power storage device
By developing polyimide-based adhesives with high repeat break energy retention, the shortcomings of polyimide-based adhesives in the prior art in terms of high capacity and high cycle characteristics are solved, and the full-solid-state battery is realized The high capacity and mechanical characteristics are improved, suitable for high-demand applications such as electric/hybrid vehicles and unmanned aerial vehicles.
Patent Information
- Application Number
- CN202080036794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-27
- Filing Date
- 2020-03-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-27
AI Technical Summary
Existing polyimide adhesives have not yet met the needs of industrial uses such as electric/hybrid vehicles and unmanned aircraft in terms of high capacity and high cycle characteristics, especially in all-solid-state batteries. There are shortcomings in terms of aspects.
A polyimide-based adhesive with a repeat break energy retention rate of more than 70%. The polyamic acid solution formed by imidation reaction is developed, combining specific tetracarboxylic acid and diamine components to form a high melting point. The adhesive, used as the adhesive for the electrode mixture paste and the negative electrode active material layer, optimizes the bonding and mechanical properties of the electrode active material.
It significantly improves the capacity retention rate and cycle characteristics of the power storage device, can maintain excellent mechanical characteristics in high temperature environments, and is suitable for all-solid-state batteries, enhancing the industrial application potential of the battery.
Smart Images

Figure BDA0003359342210000031 
Figure BDA0003359342210000032 
Figure BDA0003359342210000033
Abstract
Description
Technical Field
[0001] The invention relates to a polyimide adhesive for an electricity storage device, an electrode mixture paste, a negative electrode active material layer, a negative electrode sheet for the electricity storage device and an electricity storage device. Background Art
[0002] Power storage devices such as lithium secondary batteries have high energy density and high capacity, and are therefore widely used as driving power sources for mobile information terminals. In recent years, applications for industrial use (e.g., mounted on electric / hybrid vehicles and unmanned aerial vehicles, etc.) have been studied, and further increases in the capacity of power storage devices are being promoted. As an example of increasing capacity, with respect to the negative electrode constituting the power storage device, research has been conducted on increasing the charge / discharge capacity by using silicon or tin having a large lithium absorption amount per unit volume or alloys containing these.
[0003] However, it is known that electrode active materials with large charge / discharge capacity such as silicon or tin or alloys containing these materials cause very large volume changes accompanying charge / discharge. Therefore, when these electrode active materials are used and a negative electrode active material layer is formed using a general-purpose binder such as polyvinylidene fluoride or a rubber resin, problems such as disintegration of the negative electrode active material layer or interface peeling between the current collector and the negative electrode active material layer may occur due to the volume change of the electrode active material, resulting in a decrease in the cycle characteristics of the power storage device.
[0004] In order to solve these problems, as a method for improving the degradation of cycle characteristics caused by volume change during repeated charge / discharge, a method has been proposed, which includes using polyimide with excellent mechanical properties to bind silicon-based particles having an average particle size of 1 to 10 microns and performing heat pressing to form a negative electrode active material layer (Patent Documents 1 to 5).
[0005] It has been pointed out that in the negative electrode using polyimide as a binder disclosed in these patent documents, cracks are generated in the negative electrode active material layer due to charging / discharging, and an island structure with a space capable of absorbing volume expansion during charging / discharging is formed, which improves the capacity retention rate during repeated charging / discharging (Non-Patent Document 1).
[0006] Reference List
[0007] Patent Literature
[0008] Patent document 1: WO2004 / 004031
[0009] Patent Document 2: Japanese Patent Laid-Open Publication No. 2004-235057
[0010] Patent Document 3: Japanese Patent Laid-Open Publication No. 2003-203637
[0011] Patent Document 4: Japanese Patent Laid-Open Publication No. 2004-288520
[0012] Patent Document 5: Japanese Patent Laid-Open Publication No. 2004-022433
[0013] Non-patent literature
[0014] Non-patent document 1: Proceedings of the 48th Japan Battery Symposium, 2B23, p.238 (2007) (Yasuo Takano et al.) Summary of the invention
[0015] Technical issues
[0016] Although a certain degree of improvement in capacity and cycle characteristics can be found in conventionally disclosed power storage devices equipped with a negative electrode using polyimide as a binder, high capacity and high cycle characteristics that can meet the practical needs of industrial applications such as electric / hybrid vehicles and unmanned aerial vehicles have not yet been achieved.
[0017] In addition, since the all-solid-state battery does not have a liquid layer that acts as a buffer, the previously disclosed polyimide is insufficient to fully exhibit functions such as mechanical characteristics or battery characteristics required for the all-solid-state battery.
[0018] Therefore, an object of the present invention is to solve the above-mentioned problems and provide a polyimide-based binder for a power storage device that can further improve the battery capacity and cycle characteristics. Another object of the present invention is to provide a polyimide-based binder for a power storage device that can exhibit high capacity, cycle characteristics and mechanical properties even in an all-solid-state battery.
[0019] Solution to the problem
[0020] As a result of intensive studies by the present inventors, the present inventors have found that the cycle characteristics and mechanical characteristics of a power storage device having a large capacity are related to the fracture energy of a binder used for an electrode. Therefore, the present invention particularly relates to the following items.
[0021] [1] A polyimide-based binder for a power storage device, wherein the repeated breaking energy retention rate is 70% or more.
[0022] [2] The polyimide-based binder for a power storage device according to item 1 above, wherein the melting point of the binder is higher than 300° C. or the binder does not substantially exist.
[0023] [3] The polyimide-based binder for a storage battery device according to item 1 or 2 above, which is obtained by imidizing a polyamic acid solution containing a repeating unit represented by the following general formula (I),
[0024]
[0025] (Wherein, A is one or more tetravalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more; B is one or more divalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more.)
[0026] [4] The polyimide-based binder for a power storage device according to item 3 above, wherein in the general formula (I), 50 mol % or more of one of A and B is an open-chain aliphatic group.
[0027] [5] The polyimide binder for a power storage device according to item 3 or 4 above, wherein in the general formula (I), 50 mol % or more of A is a group represented by the following general formula (II),
[0028]
[0029] (Wherein, X is a single bond or an oxygen atom, and n is an integer from 0 to 2. If n is 1 or 2, X may be the same or different.)
[0030] [6] A resin composition for an adhesive, comprising a polyamic acid having a repeating unit represented by the following general formula (I) and a solvent, and capable of forming the polyimide-based adhesive for a power storage device described in any one of items 1 to 5 above through an imidization reaction,
[0031]
[0032] (Wherein, A is one or more tetravalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more; B is one or more divalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more.)
[0033] [7] An electrode mixture paste comprising the binder resin composition according to item 6 above and an electrode active material.
[0034] [8] A negative electrode active material layer comprising the binder for a power storage device according to any one of items 1 to 5 above and an electrode active material.
[0035] [9] A negative electrode sheet for a power storage device, comprising the negative electrode active material layer according to item 8 above formed on a surface of a current collector.
[0036]
[10] An electric storage device comprising the negative electrode sheet for an electric storage device according to item 9 above.
[0037] Advantageous Effects of the Invention
[0038] According to the present invention, a polyimide-based adhesive having a repeated breaking energy retention rate of 70% or more is provided, which can be used to improve the characteristics of a power storage device. Since such a polyimide-based adhesive exhibits suitable physical behavior for a power storage device, it can be used as an adhesive for various components of a power storage device such as a negative electrode active material layer and a negative electrode sheet. DETAILED DESCRIPTION
[0039] <Polyimide adhesive>
[0040] The polyimide-based adhesive of the present invention is characterized in that the repeated breaking energy retention rate is 70% or more.
[0041] The repeated breaking energy retention rate mentioned in the present invention refers to a value represented by the following formula.
[0042] Repeated breaking energy retention rate = (TEB 200-10 ) / (TEB0)
[0043] Wherein, (TEB0) is the initial value of tensile breaking energy calculated from the results of a tensile breaking test conducted in accordance with ASTM D882. (TEB 200-10 ) is the tensile energy at break calculated from the results of the tensile break test after repeating the 10% strain for 200 times. It can also be referred to as the 10% repeated break energy retention rate. Similarly, the retention rate after repeating the 20% strain for 200 times is called the 20% repeated break energy retention rate and can be referred to as (TEB 200-20 The retention rate after 200 repetitions of 30% strain is called 30% repeated fracture energy retention rate and can be referred to as (TEB 200-30 ).
[0044] Since the repeated fracture energy retention rate of the polyimide-based adhesive of the present invention is 70% or more, the function as a storage device can be improved while maintaining the mechanical properties. In particular, the repeated fracture energy retention rate is preferably 75% or more, 80% or more, 85% or more, and 90% or more. In other words, even when a large amount of negative electrode active materials with a large volume change rate are used, a higher repeated fracture energy retention rate can achieve a higher level of function, such as excellent cycle characteristics, without compromising the mechanical properties. Depending on the purpose of the storage device, a 20% repeated fracture energy retention rate of 60% or more, more preferably 70% or more, and especially 80% or more can be used as an additional evaluation index. Depending on the purpose of another storage device, a 30% repeated fracture energy retention rate of 50% or more, preferably 60% or more, and more preferably 70% or more can be used as an additional evaluation index.
[0045] In this way, using the repeated fracture energy retention rate, the numerical values and standards of the elements of the test conditions such as the strain value (for example, "10%" strain or "20%" strain), fracture energy value, number of repetitions and retention rate are appropriately determined according to the purpose, and they are used as an evaluation index, thereby developing a polyimide adhesive that matches the required properties of the storage device.
[0046] From another perspective, it is preferred that the melting point of the polyimide adhesive of the present invention is higher than 300° C. or that the melting point does not substantially exist. In particular, it is more preferred that the melting point exceeds 330° C. or that the melting point does not substantially exist. Since the polyimide adhesive has such characteristics, it can be appropriately used even in industrial applications that may be used in a high temperature environment.
[0047] The polyimide adhesive of the present invention refers to a polymer compound in which the repeating unit containing an imide bond accounts for 50 mol% or more of the total repeating units. The polymer capable of forming such a polyimide adhesive includes a polymer compound having a group capable of forming an imide bond in the main chain by heating or chemical reaction, and a preferred compound includes, for example, polyamic acid, in particular, a polyamic acid having the following formula (I), wherein the amount of formula (I) is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more.
[0048]
[0049] (Wherein, A is one or more tetravalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more; B is one or more divalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more.)
[0050] The chemical structure of the polyimide adhesive is preferably a polyimide adhesive containing a repeating unit represented by the following general formula (III), wherein the amount of the repeating unit is 50% or more, preferably 70% or more, and more preferably 90% or more.
[0051]
[0052] (Wherein, X1 is one or more tetravalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more; Y1 is one or more divalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more.)
[0053] The above-mentioned polyimide adhesive can be prepared by a known method using a tetracarboxylic acid component (which has the A structure in formula (I) or the X1 structure in formula (III)) and a diamine component (which has the B structure in formula (I) or the Y1 structure in formula (III)) as essential components and other components as necessary.
[0054] The tetracarboxylic acid component is not particularly limited, but preferred examples thereof include aromatic tetracarboxylic dianhydrides such as 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, diphenylsulfonetetracarboxylic dianhydride, p-terphenyltetracarboxylic dianhydride, m-terphenyltetracarboxylic dianhydride; alicyclic tetracarboxylic dianhydrides, such as cyclobutane-1,2,3,4-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride-1,2:4,5-dianhydride, bicyclo[2.2.2]oct-7-ene-2,3:5,6-tetracarboxylic dianhydride; halogenated tetracarboxylic Acid dianhydrides, such as 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride, 5,5'-[2,2,2-trifluoro-1-[3-(trifluoromethyl)phenyl]ethylidene]diphthalic anhydride, 5,5'-[2,2,3,3,3-pentafluoro-1-(trifluoromethyl)propylene]diphthalic anhydride, 1H-difluoro[3,4 -b: 3',4'-i] xanthene-1,3,7,9(11H)-tetraethyl pyrophosphate, 5,5'-oxybis[4,6,7-trifluoro-pyromellitic anhydride], 3,6-bis(trifluoromethyl)pyromellitic dianhydride, 4-(trifluoromethyl)pyromellitic dianhydride, 1,4-difluoropyromellitic dianhydride, 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorophthalic anhydride; etc. These can be used alone or in combination of two or more.
[0055] Depending on the use of the power storage device, it is preferred to use a polyimide-based binder in which A or X1 in formula (I) or formula (III) includes a group represented by the following formula (II) in an amount of 50 mol % or more.
[0056]
[0057] (Wherein, X is a single bond or an oxygen atom, and n is an integer from 0 to 2. If n is 1 or 2, X may be the same or different.)
[0058] The diamine component is not particularly limited, but preferred examples thereof include aromatic diamines such as p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 2,4-toluenediamine, 3,3'-dihydroxy-4,4'-diaminobiphenyl, bis(4-amino-3-carboxyphenyl)methane, and 2,4-diaminotoluene; halogenated diamines such as 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,3,5,6-tetrafluoro-1,4-diaminobenzene, 2,4,5,6-tetrafluoro-1,3-diaminobenzene, 2,3,5,6-tetrafluoro-1,4-benzene(dimethylamine), 2,2'-difluoro(1,1'-biphenyl)-4,4'-diamine, 4,4'-diaminooctafluorobiphenyl, 2,2-bis(4 -amino)phenyl)hexafluoropropane, 4,4'-oxybis(2,3,5,6-tetrafluoroaniline); alicyclic diamines optionally substituted with halogen, such as trans-1,4-diaminocyclohexane, cis-1,4-diaminocyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane; linear open-chain aliphatic diamines, such as 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine; and open-chain aliphatic diamines having a branched structure, wherein the above-mentioned linear open-chain aliphatic diamines are substituted with alkyl groups. These diamines can be used alone or in combination of two or more. In one embodiment of the present invention, the diamine component preferably includes an open-chain aliphatic diamine having a linear or branched structure, and the amount thereof is preferably 40 mol% or more, more preferably 50 mol% or more, still more preferably 60 mol% or more, still more preferably 70 mol% or more, and may be 100 mol%. The number of carbon atoms of the open-chain aliphatic diamine is preferably 2 or more, more preferably 6 or more, still more preferably 8 or more, for example 22 or less, preferably 18 or less. The open-chain aliphatic diamine is preferably a linear structure, but in the case of a branched structure, the number of carbon atoms of the linear portion (i.e., the number of carbon atoms bonding two amino groups) is preferably as described above.
[0059] In addition, a known dicarboxylic acid component can be added at a ratio of less than 50 mol% relative to 1 mol of tetracarboxylic acid to form an ester bond. Alternatively, various repeating units can be introduced using diamines having a polyether structure, diamines having a polysiloxane structure, or diamines having a carbonate structure. Such a structure can be appropriately determined according to the purpose and function of the power storage device.
[0060] <Resin composition for adhesive>
[0061] As one of the embodiments of the present invention, the adhesive resin composition at least includes a polyamic acid and a solvent capable of forming a polyimide adhesive, and the above-mentioned polyimide adhesive can be formed. Polyamic acid is dissolved in a solvent, and solid content concentration (polyimide conversion concentration) is preferably 5 to 45% by mass. The example of polyamic acid includes a polyamic acid comprising a repeating unit represented by the above-mentioned formula (I), wherein the amount of the repeating unit is preferably more than 50mol%, preferably more than 70mol%, more preferably more than 90mol%. The adhesive resin composition can be prepared by reacting the tetracarboxylic acid component (it has the A structure in the formula (I)) and the diamine component (it has the B structure in the formula (I)) as an essential component and other components in a solvent if necessary. The specific examples of the tetracarboxylic acid component and the diamine component are described in the above-mentioned <polyimide adhesive> chapters. The reaction solution can be used directly as an adhesive resin composition, or it can be concentrated or diluted if necessary.
[0062] Preferred solvents include nonpolar solvents, for example aromatic hydrocarbons such as xylene, toluene and ethylbenzene, aliphatic hydrocarbons such as pentane, hexane and heptane, and benzoic acid esters such as methyl benzoate, ethyl benzoate and propyl benzoate; and water, methanol, ethanol, acetone, N,N-dimethylformamide, dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam , hexamethylphosphoric triamide, 1,2-dimethoxymethane, bis(2-methoxyethyl) ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl] ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, cyclopentane, diphenyl sulfone, tetramethyl urea, anisole, m-cresol, phenol, γ-butyrolactone; in particular, water, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone and γ-butyrolactone are preferred.
[0063] Additives other than the electrode active material to be described in the next section <Electrode Mixture Paste> may be added in advance to the binder resin composition.
[0064] <Electrode compound paste>
[0065] The electrode mixture paste as one embodiment of the present invention is a composition containing polyamic acid, an electrode active material and a solvent. As the polyamic acid, a polyamic acid that can form the polyimide-based binder of the present invention can be used.
[0066] As the electrode active material in the electrode mixture paste that can be used in the present invention, known materials can be preferably used. The polyimide-based binder of the present invention can be used for the negative electrode or the positive electrode. Therefore, the electrode active material can be a negative electrode active material or a positive electrode active material. Generally, the negative electrode is more effective when using the polyimide-based binder of the present invention. In this case, the electrode active material includes a negative electrode active material. As the electrode active material, for example, a lithium metal composite oxide, carbon powder, silicon powder, tin powder, or an alloy powder containing silicon or tin is preferably used. The amount of the electrode active material in the electrode mixture paste is not particularly limited, but is generally 0.1 to 1000 times, preferably 1 to 1000 times, more preferably 5 to 1000 times, and further more preferably 10 to 1000 times based on the mass of the binder resin composition for the electrode. If the amount of the electrode active material is too large, the electrode active material cannot be sufficiently bonded to the current collector and is likely to fall off. On the other hand, if the amount of the electrode active material is too small, the negative electrode active material layer formed on the current collector has many inactive portions, and the function as an electrode may be insufficient. It can be appropriately determined according to the desired capacity.
[0067] As the negative electrode active material for an electricity storage device (such as a lithium secondary battery), lithium metal, a lithium alloy, and a carbon material capable of absorbing and releasing lithium [easily graphitizable carbon, hardly graphitizable carbon with an interplanar spacing of (002) plane of 0.37 nm or more, or graphite with an interplanar spacing of (002) surface of 0.34 nm or less], tin (elemental), a tin compound, silicon (elemental), a silicon compound, or a lithium titanate compound (such as Li4Ti5O 12 ) etc. can be used alone or in combination of two or more. In the present invention, it is preferable that the negative electrode active material at least includes tin (elemental), a tin compound, a silicon-containing electrode active material such as silicon (elemental) or a silicon compound. In particular, compared with graphite, a silicon-containing negative electrode active material such as silicon (elemental) or a silicon compound has a much larger theoretical capacity, and the volume expansion rate of the electrode active material itself during charging is also much larger.
[0068] If the polyimide-based binder for the electricity storage device of the present invention is used, the deterioration of the electrode active material due to volume expansion can be significantly suppressed, so that the characteristics of the electricity storage device in a wide temperature range can be significantly improved, not only in terms of the characteristics during use (such as cycle characteristics), but also in terms of the low-temperature characteristics and gas generation after high-temperature storage.
[0069] The type of the silicon-containing negative electrode active material is not particularly limited, and examples thereof include silicon (elemental), a silicon compound, a partially substituted product of silicon, a partially substituted product of a silicon compound, and a solid solution of a silicon compound. Specific suitable examples of the silicon compound include silicon oxide represented by the formula SiO x (0.05 < x < 1.95), and silicon carbide represented by the formula SiC ySilicon carbide represented by (0 < y < 1), silicon nitride represented by the formula SiNx (0 < z < 4 / 3), and silicon alloys which are alloys of silicon and other different elements M, etc. In the case of silicon alloys, preferred examples of the other different element M1 include at least one element selected from the group consisting of Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, and Ti.
[0070] Partially substituted products of silicon are compounds in which a part of silicon contained in silicon (elemental) and silicon compounds is substituted by other different elements M2. Specific preferred examples of the other different element M2 include B, Mg, Ni, Ti, Mo, Co, Ca, Cr, Cu, Fe, Mn, Nb, Ta, V, W, Zn, C, N, and Sn. Among these silicon-containing active materials, silicon (elemental), silicon oxides, and silicon alloys are more preferred, and silicon (elemental) and silicon oxides are further more preferred.
[0071] In order to obtain a higher capacity, the amount of the silicon-containing negative electrode active material, as the mass of net silicon in the negative electrode binder, is preferably 1% by mass or more, more preferably 5% by mass or more, still more preferably 10% by mass or more, and from the perspective of improving the cycle characteristics, it is preferably 95% by mass or less, more preferably 65% by mass or less, and further more preferably 45% by mass or less.
[0072] In addition, examples of the electrode active material (especially the negative electrode active material) for the primary lithium battery include lithium metal and lithium alloys.
[0073] Preferred solvents that can be used in the electrode binder paste of the present invention include non-polar solvents such as aromatic hydrocarbons like xylene, toluene, and ethylbenzene, aliphatic hydrocarbons like pentane, hexane, and heptane, and benzoic acid esters like methyl benzoate, ethyl benzoate, and propyl benzoate; and water, methanol, ethanol, acetone, N,N-dimethylformamide, dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, hexamethylphosphoric triamide, 1,2-dimethoxymethane, bis(2-methoxyethyl) ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl] ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, sulfolane, diphenyl sulfone, tetramethylurea, anisole, m-cresol, phenol, γ-butyrolactone; in particular, water, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone are preferred.
[0074] As the solvent, the solvent in the binder resin composition can be directly used, or it can be concentrated when necessary or additional solvents can be added to provide an appropriate coating concentration.
[0075] In the electrode mixture paste of the present invention, when it is made into an aqueous solvent system, it is preferably contained a pyridine compound or an imidazole compound. Therefore, the swelling degree of the obtained polyimide relative to the electrolyte solution can be made smaller, and the elongation at break and the fracture energy can be made larger. In addition, the heat treatment temperature for obtaining the negative electrode active material layer can be reduced. The pyridine compound is a compound having a pyridine portion in its chemical structure, and preferred examples thereof include pyridine, 3-pyridinol, quinoline, isoquinoline, quinoxaline, 6-tert-butylquinoline, acridine, 6-quinolinecarboxylic acid, 3,4-dimethylpyridine and pyridazine, etc. These pyridine compounds can be used alone or in combination of two or more. Examples of imidazole compounds include 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 4-ethyl-2-methylimidazole and 1-methyl-4-ethylimidazole, etc. Imidazoles can be used alone or in a mixture of multiple species.
[0076] The amount of the pyridine compound to be added is not limited, but relative to 1 mole of the amic acid repeating unit of the polyamic acid, it is preferably 0.05 to 2.0 molar equivalents, more preferably 0.1 to 1.0 molar equivalents. If the amount added is outside this range, it may be difficult to use an aqueous solvent system. The amount of the imidazole compound to be added is not limited, but relative to 1 mole of the amic acid repeating unit of the polyamic acid, it is 1.6 molar equivalents or more, more preferably 2.0 molar equivalents or more, and even more preferably 2.4 molar equivalents or more.
[0077] In the electrode mixture paste of the present invention, known additives can be added if necessary. For example, adhesives other than negative electrode conductive agent, alkali, surfactant, viscosity modifier, conductive aid, silane coupling agent, polyimide adhesives etc. can be used, as long as the effect of the present invention is not impaired.
[0078] The negative electrode conductive agent is not particularly limited as long as it is an electronic conductive material that does not cause chemical changes, but it is preferred to use a metal powder (such as copper, nickel, titanium or aluminum) or a carbon material, etc. The carbon material used as the conductive agent and the negative electrode active material preferably includes graphite, such as natural graphite (scaly graphite, etc.), artificial graphite and other graphites; one or more carbon blacks selected from acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; and fibrous carbon powders, such as carbon nanotubes and carbon fibers.
[0079] In addition, it is more preferred that the negative electrode conductive agent can be appropriately mixed and used in such a mixture, such as graphite and carbon black, graphite and fibrous carbon powder, or carbon black and fibrous carbon powder. In particular, fibrous carbon powder is preferably used because it has the effect of reducing the use of a conductive agent with a large specific surface area to ensure conductivity. The carbon material is used as a conductive agent or a negative electrode active material, and the amount of the carbon material added to the negative electrode mixture is preferably 1 to 90 mass %, more preferably 10 to 70 mass %.
[0080] When a carbon material is mixed with a silicon-containing negative electrode active material and used as a negative electrode conductive agent, from the perspective of improved cycle characteristics caused by the effect of enhancing electronic conductivity by mixing with the carbon material, the ratio of the silicon-containing negative electrode active material to the carbon material is such that the carbon material is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total net mass of silicon in the silicon-containing negative electrode active material in the negative electrode mixture. In addition, if the ratio of the carbon material mixed with the silicon-containing negative electrode active material is too large, the amount of the silicon-containing negative electrode active material in the negative electrode mixture layer may be reduced, and the effect of increasing the capacity may be reduced. Based on the total mass of the carbon material, the net mass of silicon in the silicon-containing negative electrode active material is preferably 1% by mass or more, more preferably 2% by mass or more, and further more preferably 5% by mass or more. In addition, it is more preferred that, if necessary, the conductive agent is compounded by premixing with the silicon-containing active material and performing appropriate heat treatment.
[0081] When graphite is used, it is more preferred to use a carbon material having a graphite-type crystal structure, wherein the interplanar spacing (d002) of the graphite lattice plane (002) is 0.340 nm (nanometer) or less, particularly 0.335 nm to 0.337 nm. In particular, preferred are artificial graphite particles having a block structure in which a plurality of flat graphite fine particles are assembled or bonded to each other in a non-parallel manner; or spherical particles of scaly natural graphite obtained by repeatedly applying mechanical actions (e.g., compression, friction, and shearing forces).
[0082] The ratio I(110) / I(004) is preferably 0.01 or more because the electrochemical characteristics in a wider temperature range are improved, and is more preferably 0.05 or more, and further more preferably 0.1 or more, wherein I(110) / I(004) is a ratio of the peak intensity I(110) of the (110) plane of the graphite crystal to the peak intensity I(004) of the (004) plane, which is obtained by pressing the negative electrode into a temperature of 1.5 g / cm 3 The above density (excluding the current collector) is determined by X-ray diffraction measurement values of the negative electrode sheet measured. In addition, the upper limit of the peak intensity ratio I(110) / I(004) is preferably less than 0.5, and more preferably less than 0.3, because excessive processing can reduce the crystallinity and discharge capacity of the battery.
[0083] In addition, it is preferred that the high crystalline carbon material (core material) is coated with a carbon material having a lower crystallinity than the core material, because the electrochemical properties in a wide temperature range are further improved. The crystallinity of the coated carbon material can be confirmed by TEM. When a high crystalline carbon material is used, it reacts with a non-aqueous electrolyte solution during charging, and the characteristics of the power storage device in a wide temperature range (such as low temperature characteristics and gas generation after high temperature storage) tend to deteriorate due to an increase in interface resistance. However, if the polyimide-based adhesive for the power storage device of the present invention is used, the characteristics of these power storage devices are improved.
[0084] When the polyimide binder for power storage devices of the present invention is used in combination with other binders, the ratio of the mass of the other binder to the total mass of the binder is preferably 1 to 95 mass %, more preferably 5 to 45 mass %.
[0085] Examples of binders other than the polyimide-based binder for the power storage device of the present invention include polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene rubber, butadiene rubber, nitrile rubber, polyacrylonitrile, ethylene vinyl alcohol copolymer resin, ethylene propylene diene rubber, polyurethane, polyacrylic acid, polyamide, polyacrylate, polyvinyl ether, fluororubber, carboxymethyl cellulose, and sodium carboxymethyl cellulose.
[0086] In addition, the electrode mixture paste of the present invention may further include a solid electrolyte. Examples of the solid electrolyte include oxide-based solid electrolytes, such as La having a perovskite crystal. 0.51 Li 0.34 TiO 2.94 , Li7La3Zr2O with garnet crystals 12 , Li with NASICON-type crystal 1.3 Al 0.3 Ti 1.7 (PO4)3 and amorphous LiPON(Li 2.9 PO 3.3 N 0.46 ); and sulfide-based solid electrolytes, such as Li2S-SiS2-based materials and Li2S-P2S5-based materials.
[0087] The electrode mixture paste of the present invention can be prepared by applying the above-mentioned components to a known manufacturing method and preparing a uniform composition by adding, stirring and mixing, etc. For example, a solution or dispersion in which a polyimide-based binder and a solvent are mixed is prepared, and then various additives are added and mixed, thereby preparing the electrode mixture paste.
[0088] <Negative Electrode Active Material Layer>
[0089] The negative electrode active material layer as one of the embodiments of the present invention can be manufactured by forming an electrode mixture paste into a film using a known method. Although not particularly limited, one example thereof includes preparing an electrode mixture paste including a polyimide-based binder, a solvent, and a negative electrode active material, casting or coating the electrode mixture paste on a metal foil or a plastic film, heat treating it to remove the solvent, and performing an imidization reaction if necessary to obtain a layer. In particular, a negative electrode sheet for a storage device can be manufactured by forming a negative electrode active material layer on a conductive current collector formed of a metal foil such as an aluminum foil.
[0090] The thickness of the negative electrode active material layer of the present invention can be appropriately determined according to the purpose and required capacity of the power storage device. Although not limited, it is preferably used in the range of 0.1 μm to 500 μm, for example. In particular, it is more preferably 1 μm or more, 10 μm or more, and 20 μm or more, and more preferably 300 μm or less, 100 μm or less, and 50 μm or less.
[0091] <Negative electrode sheet for power storage device>
[0092] The negative electrode sheet for a power storage device as one of the embodiments of the present invention is a sheet formed by casting or coating an electrode mixture paste on a current collector to form an active material layer, wherein the electrode mixture paste is a mixture of the polyimide-based binder for a power storage device of the present invention, a negative electrode active material, and optional components such as a conductive agent, etc. Preferably, the negative electrode sheet for a power storage device of the present invention is a negative electrode sheet formed by casting or coating a negative electrode mixture including the polyimide-based binder for a power storage device of the present invention, a silicon-containing negative electrode active material, and a carbon material on a copper current collector to form a negative electrode active material layer.
[0093] <Positive Electrode Active Material>
[0094] As a positive electrode active material for an electricity storage device (particularly a lithium secondary battery), a composite metal oxide containing at least one selected from cobalt, manganese and nickel and lithium is used.
[0095] These positive electrode active materials can be used alone or in combination of two or more. Examples of such lithium composite metal oxides include those selected from LiCoO2, LiMn2O4, LiNiO2, LiCo 1-x Ni x O2(0.01 <x<1)、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2、LiNi 1 / 2Mn 3 / 2 O4 and LiCo 0.98 Mg 0.02O2. Furthermore, these may be used in combination, such as LiCoO2 and LiMn2O4, LiCoO2 and LiNiO2, and LiMn2O4 and LiNiO2.
[0096] In addition, a part of the lithium composite metal oxide may be replaced by other elements in order to improve safety and cycle characteristics during overcharge, or to enable use at a charging potential of 4.3 V or more. For example, a part of cobalt, manganese, and nickel may be replaced by at least one or more elements such as Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn, Cu, Bi, Mo, and La. Or a part of O may be replaced by S or F, or a coating may be formed from a compound containing these other elements.
[0097] Among them, preferred are lithium composite metal oxides that can be operated at a positive electrode charging potential of 4.3V or more relative to Li in a fully charged state, such as LiCoO2, LiMn2O4 and LiNiO2. More preferred are lithium composite metal oxides that can be operated at 4.4V or more, such as lithium cobalt oxides substituted with different elements, such as LiCo 1-x M x O2 (wherein M is one or more elements selected from Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn and Cu, 0.001≤x≤0.05), and a lithium composite metal oxide in which the ratio of nickel atoms and manganese atoms to all metal elements other than lithium atoms is 50 atomic % or more and 100 atomic % or less, such as LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.5 Mn 0.3 Co 0.2 O2、LiNi 1 / 2 Mn 3 / 2 O4 and solid solutions of Li2MnO3 and LiMo2 (wherein M is a transition metal such as Co, Ni, Mn, and Fe, etc.). When using lithium composite metal oxides operating at high charging voltages, the characteristics of the storage device tend to deteriorate when used in a wide temperature range due to the reaction with the electrolyte solution during charging. However, if the polyimide adhesive for the storage device of the present invention is used, the degradation of the characteristics of these storage devices can be suppressed.
[0098] In addition, as the positive electrode active material, lithium-containing olivine-type phosphates may also be used. In particular, lithium-containing olivine-type phosphates containing at least one selected from iron, cobalt, nickel and manganese are preferred. Specific preferred examples thereof include one or more selected from LiFePO4, LiCoPO4, LiNiO4 and LiMnPO4.
[0099] Some of these lithium-containing olivine-type phosphates may be replaced with other elements, and a portion of iron, cobalt, nickel and manganese may be replaced with one or more elements selected from Co, Mn, Ni, Mg, Al, B, Ti, V, Nb, Cu, Zn, Mo, Ca, Sr, W and Zr, or a coating may be formed by a compound or carbon material containing these other elements. Among them, LiFePO4 or LiMnPO4 is preferred. In addition, the lithium-containing olivine-type phosphate may be mixed with the above-mentioned positive electrode active material, for example.
[0100] In addition, examples of positive electrodes for lithium primary batteries include oxides or chalcogenides of one or more metal elements, such as CuO, Cu2O, Ag2O, Ag2CrO4, CuS, CuSO4, TiO2, TiS2, SiO2, SnO, V2O5, V6O 12 , VO x , Nb2O5, Bi2O3, Bi2Pb2O5, Sb2O3, CrO3, Cr2O3, MoO3, WO3, SeO2, MnO2, Mn2O3, Fe2O3, FeO, Fe3O4, Ni2O3, NiO, CoO3 and CoO; sulfides, such as SO2, SOCl2; and the general formula (CF x ) n Among them, MnO2, V2O5 and graphite fluoride are preferred.
[0101] <Positive Electrode Conductive Agent>
[0102] There is no particular limitation on the positive electrode conductor as long as it is an electronic conductive material that does not cause chemical changes. Preferred examples thereof include graphite, such as natural graphite (scaly graphite, etc.), artificial graphite and other graphites; one or more carbon blacks selected from acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; and fibrous carbon powders, such as carbon nanotubes and carbon fibers. In addition, it is more preferred that the positive electrode conductor can be appropriately mixed and used in such a mixture, such as graphite and carbon black, graphite and fibrous carbon powder, or carbon black and fibrous carbon powder. The amount of the conductive agent added to the positive electrode mixture is preferably 1 to 10% by mass, more preferably 2 to 5% by mass.
[0103] <Positive Electrode Binder>
[0104] As the positive electrode binder, the polyimide-based binder for the storage device of the present invention can be used, but other binders can also be used, and examples thereof include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), a copolymer of styrene and butadiene (SBR), a copolymer of acrylonitrile and butadiene (NBR), carboxymethyl cellulose (CMC) or ethylene propylene diene terpolymer.
[0105] Furthermore, the polyimide-based binder for a power storage device of the present invention may be used in combination with other binders, but preferred embodiments thereof are the same as those described in the section <Negative Electrode Binder>.
[0106] <Positive electrode sheet for power storage device>
[0107] The positive electrode sheet for a power storage device is a sheet formed by casting or coating an electrode mixture paste, which is a mixture of a positive electrode binder, a positive electrode active material, and optional components such as a conductive agent, on a current collector to form an active material layer.
[0108] <Electrical Storage Device>
[0109] The power storage device as one of the embodiments of the present invention includes the negative electrode sheet for the power storage device. For other configurations, known configurations required for the power storage device can be adopted. The power storage device of the present invention includes a lithium battery, a double-layer capacitor, a lithium ion capacitor, etc. As another aspect, the negative electrode sheet for the power storage device can be made into a sheet with high capacity and excellent mechanical properties, so it can be applied to all-solid-state batteries, etc.
[0110] Example
[0111] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0112] The methods for measuring the characteristics in the following examples are shown below.
[0113] <Tensile Breaking Energy>
[0114] The tensile breaking energy was calculated from the results of the tensile breaking test conducted in accordance with ASTM D882.
[0115] <10% repeated breaking energy retention rate>
[0116] The initial value of the tensile breaking energy is defined as (TEB0), and the tensile breaking energy calculated from the result of the tensile breaking test after repeating the 10% strain 200 times is defined as (TEB 200-10 ). Calculate according to the following formula.
[0117] 10% repeated breaking energy retention rate = (TEB 200-10 ) / (TEB0)
[0118] <20% repeated breaking energy retention rate>
[0119] The initial value of the tensile breaking energy is defined as (TEB0), and the tensile breaking energy calculated from the result of the tensile breaking test after repeating the 20% strain 200 times is defined as (TEB 200-20). Calculate according to the following formula.
[0120] 20% repeated breaking energy retention rate = (TEB 200-20 ) / (TEB0)
[0121] <30% repeated breaking energy retention rate>
[0122] The initial value of the tensile breaking energy is defined as (TEB0), and the tensile breaking energy calculated from the result of the tensile breaking test after repeating the 30% strain 200 times is defined as (TEB 200-30 ). Calculate according to the following formula.
[0123] 30% repeated breaking energy retention rate = (TEB 200-30 ) / (TEB0)
[0124] Abbreviations of compounds used in the following examples will be described.
[0125] s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0126] ODPA: 4,4'-oxydiphthalic anhydride
[0127] PMDA: Pyromellitic Dianhydride
[0128] ODA: 4,4'-diaminodiphenyl ether
[0129] PPD: p-phenylenediamine
[0130] DMD: decamethylenediamine
[0131] NMP: N-methyl-2-pyrrolidone
[0132] [Example 1]
[0133] 400 g of NMP as a solvent was added to a glass reaction container equipped with a stirrer and a nitrogen introduction / exhaust tube having an inner volume of 500 mL, and 40.49 g (0.202 mol) of ODA and 59.51 g (0.202 mol) of s-BPDA were added, and stirred at 50° C. for 10 hours to obtain a polyimide precursor for a power storage device having a solid concentration of 18.2% by mass and a solution viscosity of 5.0 Pa·s. The obtained polyimide precursor for a power storage device was used directly as a resin composition for an adhesive.
[0134] The obtained polyimide precursor for the storage device is coated on a glass plate of the substrate by a rod coater, and the coating film is defoamed and pre-dried at 25°C for 30 minutes under reduced pressure, and then placed in a hot air dryer under a nitrogen atmosphere at normal pressure, and heat treated at 120°C for 30 minutes, 150°C for 10 minutes, 200°C for 10 minutes, 250°C for 10 minutes, and 350°C for 10 minutes to form an adhesive resin film with a thickness of 30 μm.
[0135] The (TEB0) of the obtained film is 163MJ / m 3 , (TEB 200-10 ) is 151MJ / m 3 , 10% repeated fracture energy retention rate is 93%.
[0136] [Example 2]
[0137] Into a glass reaction container with an inner volume of 500 mL equipped with a stirrer and a nitrogen introduction / exhaust tube, 425 g of NMP was added as a solvent, and 13.45 g (0.078 mol) of DMD, 15.63 g (0.078 mol) of ODA and 45.92 g (0.156 mol) of s-BPDA were added, and stirred at 50° C. for 10 hours to obtain a polyimide precursor for a storage device having a solid concentration of 13.3% by mass and a solution viscosity of 3.4 Pa·s.
[0138] The obtained polyimide precursor for the storage device is coated on a glass plate of the substrate by a rod coater, and the coating film is defoamed and pre-dried at 25°C for 30 minutes under reduced pressure, and then placed in a hot air dryer under a nitrogen atmosphere at normal pressure, and heat treated at 120°C for 30 minutes, 150°C for 10 minutes, and 200°C for 120 minutes to form an adhesive resin film with a thickness of 30 μm.
[0139] The (TEB0) of the obtained film is 181 MJ / m 3 , (TEB 200-10 ) is 179MJ / m 3 , (TEB 200-20 ) is 159MJ / m 3 , (TEB 200-30 ) is 132MJ / m 3 The energy retention rate of 10% repeated fracture is 99%, the energy retention rate of 20% repeated fracture is 88%, and the energy retention rate of 30% repeated fracture is 73%.
[0140] [Example 3]
[0141] Into a glass reaction container having an inner volume of 500 mL equipped with a stirrer and a nitrogen introduction / exhaust tube, 400 g of NMP was added as a solvent, and 17.35 g (0.101 mol) of DMD, 20.17 g (0.101 mol) of ODA and 62.48 g (0.201 mol) of ODPA were added, and stirred at 50° C. for 10 hours to obtain a polyimide precursor for a storage device having a solid concentration of 18.0% by mass and a solution viscosity of 5.7 Pa·s.
[0142] The obtained polyimide precursor for the storage device is coated on a glass plate of the substrate by a rod coater, and the coating film is defoamed and pre-dried at 25°C for 30 minutes under reduced pressure, and then placed in a hot air dryer under a nitrogen atmosphere at normal pressure, and heat treated at 120°C for 30 minutes, 150°C for 10 minutes, and 200°C for 120 minutes to form an adhesive resin film with a thickness of 30 μm.
[0143] The (TEB0) of the obtained film is 147MJ / m 3 , (TEB 200-10 ) is 140MJ / m 3 , 10% repeated fracture energy retention rate is 96%.
[0144] [Example 4]
[0145] Into a glass reaction container having an inner volume of 500 mL equipped with a stirrer and a nitrogen introduction / exhaust tube, 400 g of NMP was added as a solvent, and 32.56 g (0.163 mol) of ODA, 4.40 g (0.041 mol) of PPD and 63.05 g (0.203 mol) of ODPA were added, and stirred at 50° C. for 10 hours to obtain a polyimide precursor for a storage device having a solid concentration of 18.1% by mass and a solution viscosity of 6.3 Pa·s.
[0146] The obtained polyimide precursor for the storage device is coated on a glass plate of the substrate by a rod coater, and the coating film is defoamed and pre-dried at 25°C for 30 minutes under reduced pressure, and then placed in a hot air dryer under a nitrogen atmosphere at normal pressure, and heat treated at 120°C for 30 minutes, 150°C for 10 minutes, and 200°C for 120 minutes to form an adhesive resin film with a thickness of 30 μm.
[0147] The (TEB0) of the obtained film is 140MJ / m 3 , (TEB 200-10 ) is 139MJ / m 3 , 10% repeated fracture energy retention rate is 99%.
[0148] [Comparative Example 1]
[0149] To a glass reaction container with an inner volume of 500 mL equipped with a stirrer and a nitrogen introduction / exhaust tube, 400 g of NMP was added as a solvent, and 47.85 g (0.239 mol) of ODA and 52.15 g (0.239 mol) of PMDA were added, and stirred at 50° C. for 10 hours to obtain a polyimide precursor having a solid concentration of 18.0% by mass and a solution viscosity of 4.8 Pa·s.
[0150] The obtained polyimide precursor was coated on a glass plate of the substrate by a rod coater, and the coating film was defoamed and pre-dried at 25°C for 30 minutes under reduced pressure, and then placed in a hot air dryer under a nitrogen atmosphere at normal pressure, and heat-treated at 120°C for 30 minutes, 150°C for 10 minutes, 200°C for 10 minutes, 250°C for 10 minutes, and 350°C for 10 minutes to form a resin film with a thickness of 30 μm.
[0151] The (TEB0) of the obtained film is 138MJ / m 3 , (TEB 200-10 ) is 84MJ / m 3 , the 10% repeated fracture energy retention rate is 61%.
[0152] [Manufacturing of lithium-ion secondary batteries]
[0153] 93 mass% LiNi 0.5 Mn 0.3 Co 0.2 O2 and 3% by mass of acetylene black (conductive agent) were mixed and added to a solution in which 4% by mass of polyvinylidene fluoride (binder) was preliminarily dissolved in 1-methyl-2-pyrrolidone and mixed therewith to prepare a positive electrode mixture paste. The positive electrode mixture paste was applied to one side of an aluminum foil (current collector), dried, pressed and punched into a predetermined size to form a positive electrode sheet (positive electrode No. 1).
[0154] 15% by mass (as solids) of the binder resin composition obtained in the examples and comparative examples, 60% by mass of elemental silicon (Si), 20% by mass of artificial graphite (d002 = 0.335 nm) and 5% by mass of fibrous carbon powder (diameter; 12 nm, fiber length; 114 nm) were used to prepare a negative electrode mixture paste. The negative electrode mixture paste was applied to one side of a copper foil (current collector), and heated, dried, pressed and punched into a predetermined size to prepare a negative electrode sheet. Then, the positive electrode sheet, the separator made of a microporous polyethylene film and the negative electrode sheet were stacked in sequence, and a non-aqueous electrolyte solution was added to prepare a 2032-type button battery. The non-aqueous electrolyte solution has a composition comprising 1M LiPF6+0.05M LiPO2F2 dissolved in ethylene carbonate / ethyl methyl carbonate / diethyl carbonate / 4-fluoro-1,3-dioxolane-2-one (volume ratio 25 / 30 / 40 / 5).
[0155] Using the manufactured button cell, the battery was charged to a final voltage of 4.2 V at a constant current and a constant voltage of 1 C for 3 hours in a constant temperature container at 25° C., and discharged to a final voltage of 2.75 V at a constant current of 1 C. This cycle was repeated 200 times, and the capacity retention rate was calculated from the first and 200th discharge capacities.
[0156] It was found that the polyimide-based adhesive obtained from the adhesive resin composition of Examples 1 to 4 had a large capacity retention rate compared to conventional polyimides (e.g., the polyimide-based adhesive obtained from the adhesive resin composition of Comparative Example 1). Therefore, it was confirmed that the use of the polyimide-based adhesive for a power storage device of the present invention can significantly improve the characteristics of a power storage device having a negative electrode using Si or SiO as an electrode active material to obtain a higher capacity.
Claims
1. A polyimide adhesive for a storage device, obtained by imidizing a polyamic acid solution containing a repeating unit represented by the following general formula (I), wherein 50 mol % or more of one of the groups A and B in the general formula (I) is an open-chain aliphatic group, in, A is one or more tetravalent groups selected from groups having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more; B is one or more divalent groups selected from groups having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or two or more, and The polyimide adhesive for a power storage device has a repeated breaking energy retention rate defined by the following formula of 70% or more: Repeated breaking energy retention rate = (TEB 200-10 ) / (TEB0) Wherein, (TEB0) is the initial value of the tensile breaking energy calculated from the result of the tensile breaking test conducted in accordance with ASTM D882, (TEB 200-10 ) is the tensile breaking energy calculated from the results of a tensile breaking test after repeating 10% strain 200 times. 2 . The polyimide-based binder for a power storage device according to claim 1 , wherein the melting point of the binder is higher than 300° C. or does not exist.
3. The polyimide-based binder for a power storage device according to claim 1, wherein in the general formula (I), 50 mol % or more of A is a group represented by the following general formula (II): in, X is a single bond or an oxygen atom, and n is an integer from 0 to 2. If n is 1 or 2, X may be the same or different.
4. A resin composition for an adhesive, comprising a polyamic acid having repeating units represented by the following general formula (I) and in which 50 mol % or more of one of A and B in the general formula (I) is an open-chain aliphatic group, and a solvent, and capable of forming the polyimide adhesive for a storage device according to claim 1 through an imidization reaction, in, A is one or more tetravalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or there may be two or more of them; B is one or more divalent groups selected from a group having an aromatic ring, an open-chain aliphatic group or a group having an alicyclic structure, which may be substituted by halogen, and may be the same or there may be two or more of them. 5 . An electrode mixture paste comprising the binder resin composition according to claim 4 and an electrode active material. 6 . A negative electrode active material layer comprising the binder for a power storage device according to claim 1 and an electrode active material. 7 . A negative electrode sheet for a power storage device, comprising the negative electrode active material layer according to claim 6 formed on a surface of a current collector. 8 . An electric storage device comprising the negative electrode sheet for an electric storage device according to claim 7 .
